THE EFFECT OF SERVICE QUALITY AND EMOTIONAL CLOSENESS TO CLIENT LOYALTY AT STIFIn MEDAN - Dona Dona; Syamsul Bahri (Jurnal Ekonomi, 2023)
The objective of this research was to establish whether client loyalty at STIFIn Medan is influenced by service quality and emotional closeness. The sample of this study was 133 respondents. Sampling using random sampling namely the determination of samples that provide equal opportunities for each member of the population to be sampled. using multiple regression tests to analyze data and the coefficient of determination (R2) to assess hypotheses, partial test (t test), and simultaneous test (F test), while data processing using SPSS 22. The results showed that partially service quality and emotional closeness affect client loyalty, and simultaneously service quality and emotional closeness affect client loyalty.